Flexible magnifying endoscopy with narrow band imaging for the diagnosis of uterine cervical tumors: A cooperative study among gastrointestinal endoscopists and gynecologists to explore a novel microvascular classification system - Nishiyama, Noriko (Oncol Lett, 2017)
Narrow band imaging with magnifying endoscopy (NBI-ME), which is useful for the assessment of micro-vessels, has excellent diagnostic potential for early gastrointestinal epithelial neoplasia. Conventional diagnostic tools for uterine cervical epithelial tumors are still unsatisfactory. An accurate diagnostic tool for uterine cervical epithelial tumors is required to preserve the reproductive ability of young women with uterine cervical tumors. Flexible NBI-ME was performed in patients with cervical squamous cell lesions that required further examinations based on their Pap smear results (cytology ≥ low-grade squamous intraepithelial lesion) at Kagawa University Hospital between April 2014 and April 2015. NBI-ME results concordant with the punch biopsy sites were compared with the histological results. A retrospective review of the NBI-ME images identified abnormal NBI-ME results regarding micro-vascular patterns. All images were categorized as having abnormal features. NBI-ME revealed the following vascular pattern differences of different stage tumors: Dot-like vessels without irregular arrangements and high density in cervical intraepithelial neoplasia (CIN) CIN1-CIN2; dot-like vessels with irregular arrangements and high density in CIN3-carcinoma in situ; crawling vessels in minimum invasive cancer; and willow branch vessels and new tumor vessels in invasive cancer. NBI-ME may be an effective diagnostic tool for uterine cervical epithelial tumors, which may lead to the establishment of a novel classification system.